Effect of Aging on Glycemic Status during Pregnancy - Mahmuda, Shahin; Akhtar, Nasima; Sardar, Mijanur Rahman; Asafudullah, SM (TAJ: Journal of Teachers Association, 2018)
Background: Pregnancy is associated with profound alteration in maternal metabolism. But this altered glucose homeostasis during pregnancy causes significant increase in feto-maternal abnormalities. This risk may increase due to maternal ageing. Objective: To assess the effect of ageing during pregnancy on fasting and postprandial glucose and glycated hemoglobin level in order to find out the risk of gestational diabetes. Methods: This cross sectional study was carried out in the department of Physiology, Rajshahi medical college, between the periods of January 2010 to December 2010. Three hundred pregnant woman aged 15 to 39 years were enrolled in the study and were divided into 5 different age groups, fasting and postprandial blood glucose and glycated hemoglobin levels were estimated by standard laboratory procedure. Data were analyzed by using SPSS computer software program and the test for significance was done by Chi-square test. Result: About 43% of pregnant women belonging to age group 35-39 years were detected as gestational diabetes mellitus, whereas less than 1% pregnant women among 20-24 years age group was detected as GDM. Blood sugar level both FBS and PPBS of all the pregnant women of age group 15-19 years are within normal limit. Conclusion: Results of the study indicates that the incidence of GDM was proportionate to increasing maternal age. So close monitoring of older pregnant women should be done to avoid feto-maternal complications. TAJ 2017; 30(2): 60-64